2020
DOI: 10.1364/osac.391540
|View full text |Cite
|
Sign up to set email alerts
|

Upper bound of efficiency for Smith-Purcell emission and evanescent-to-propagating wave conversion in metal-groove metasurfaces

Abstract: When a charged particle moves parallel and close to the surface of a metasurface, intense Smith-Purcell radiation can be observed at resonant frequencies. Here, we present a systematic investigation on the Smith-Purcell radiation and evanescent-to-propagating wave conversion in metal-groove metasurfaces. Based on a coupled mode theory, analytic formulas are derived for the resonant frequency, Q-factor, and wave conversion efficiency at resonant frequency. The accuracy of the formulas is verified by numerical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…It is noticeable that the dispersion relation can also be easily derived using the above formulation. In the absence of incident field, equations ( 27) and (28) become…”
Section: Theoretical Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noticeable that the dispersion relation can also be easily derived using the above formulation. In the absence of incident field, equations ( 27) and (28) become…”
Section: Theoretical Modelingmentioning
confidence: 99%
“…To date, most studies of SPR used metallic structures. Previous studies have shown that for a metallic grating, the SPR can be enhanced by the resonance effect of the TEM waveguide mode in the presence of a small groove width [26][27][28]. The enhanced SPR, which is called special SPR (S-SPR), has a narrow spectrum and radiates at specific directions.…”
Section: Introductionmentioning
confidence: 99%
“…Tamm and Frank have developed a theoretical approach to describe the classical ChR characteristics 14 . Recently more advanced ChR mechanisms have been considered for intense radiation generation including excitation of structural materials such as metamaterials 15 , gratings 8 , 9 , 16 , or photonic crystals 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Those currents give rise to an entire family of polarization radiation mechanisms that have been widely applied for both charged particle beam diagnostics and the generation of intense EM radiation beams, e.g. transition radiation 2,3 , diffraction radiation 4,5 , Smith-Purcell radiation [6][7][8][9] , and parametric X-ray radiation 10 . More recently it has been proposed to use plasmons generated by the field of passing particle in a thin conducting material to reinforce polarization radiation photon yield at well-defined frequencies 11,12 .…”
mentioning
confidence: 99%